Generation Z and Leadership Readiness in Volatility, Uncertainty, Complexity, and Ambiguity (VUCA) Environments: A Qualitative Exploration across Key Sectors (The International Research Journal of Management Science, 2025)
Purpose: Gen-Z is entering the workforce in increasing numbers; however, their ability to adapt and prepare for leadership roles under VUCA conditions remains insufficiently examined. This study investigates how Gen-Z professionals understand and experience leadership readiness within VUCA business contexts.Design/Methodology/Approach: A  qualitative phenomenological design was used to capture the lived experiences of Gen-Z professionals. Data was gathered through 12 semi-structured interviews of emerging leaders across banking, tourism, trade, and hospitality. Interview data were thematically analyzed.Findings: Leadership readiness among Gen-Z is promising and incomplete when considered in relation to the demands of a VUCA environment. At the individual level, emotional intelligence, resilience, and digital competence emerged as critical traits. At the developmental level, mentorship, peer collaboration, and learning agility were central to growth. At the contextual level, organizational culture, hierarchical structures, and environmental turbulence acted as key enablers or barriers.Practical Implications: The findings suggest the urgency of leadership development strategies tailored to Gen-Z. Organizations should invest in institutional structures for a continuous and structured mentoring culture, cross-generational knowledge-sharing stages, and flexible working cultures that inspire investigation while reinforcing resilience.Originality/Value: It provides pragmatic insights into an emerging leadership regime whose preparedness for VUCA contexts remains relatively unexplored.